(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This paper examines the current trends, challenges in the Food &Beverage (F&B) Service Industry with special focus on the future prospectsof the industry. The changing in customer attitudes through educationalknowledge has led to the increased in healthier eating including the restaurantfood and others foodservice operation. Dining in a restaurant for them is notonly to satisfy the hunger but for them such eating experience is to gainknowledge about the local cuisine and of the destinations culture. The use ofinternet enabled mobile devices such as cell phones, palm pilots, blackberriesand Personal Digital Assistants (PDAs) has steadily increased and helps therestaurant customers to use the services online. Manpower shortage is findingto be the most difficult challenge by the food service industry. Further it isrevealed that organizations may face serious obstacles when outsourcing theactivities if adequate attention is not paid to the remaining employees. As thefood service industry in India grows, more and more international chains willcome in India and attempt to establish franchise networks. The industry willcome up with the new trends which help in guest satisfaction. The food serviceindustry is expected to be the largest beneficiary of the expanding F&Bindustry.